Peningkatan Kualitas Throat Weld pada Hasil Penetrasi Produk Bracket Spring dengan Metode DMAIC di Perusahaan Komponen Otomotif - Prahara, Rahayu Budi; Wahyudi, Wahyudi; Sahrirudin, Wandi (Jurnal Optimalisasi, 2025)
Component Automotive Indutry is a manufacturing company that focuses on making chassis frames and press parts, with the production delivered to ATPM (Single Agent Brand Holder) customers. One of the production lines at Component Automotive Indutry is the non-frame sub-assembly using welding robot A, which produces various components, such as spring bracket no. 1, spring bracket no. 2, spring bracket no. 3, and engine mounting bracket. To ensure welding quality, Component Automotive Indutry conducts various tests, including welding penetration tests, which are carried out in the company's laboratory using samples in accordance with the Quality Control Process Chart (QCPC). Over the past three months, the penetration test results on the spring no. 1 bracket showed a penetration rate of 82%, which did not meet the ATPM company's minimum standard of 100%. Faced with this problem, this study uses the DMAIC (Define, Measure, Analyze, Improve, Control) method to conduct process analysis and improvement. In the Define stage, the main problem identified was item throat penetration that did not meet the standard. The Measure stage then set a target of 100% penetration improvement. In the Analyze stage, the main causes of penetration instability were analyzed, identifying the vertical welding position as the main causal factor. The Improve stage was carried out by changing the welding position of the throat item from vertical to horizontal using a temporary jig. This change aimed to maintain gravity stability and achieve consistent penetration in accordance with the minimum standard of 4.2 mm. After conducting 9 trials, the improvement results showed that the welding penetration achieved 100% stability. The Control phase ensured that the implemented changes were continuously maintained to ensure consistent quality. This study concludes that changing the welding position from vertical to horizontal is significant in improving the quality and consistency of weld penetration on bracket spring no. 1 products at Component Automotive Indutry The findings underscore the importance of evaluating and adjusting the welding process to meet the quality standards set by customers.